The effect of perceived usefulness, perceived ease of use, trust and perceived risk toward E-wallet usage / Akmal Nashren Abd Malik and Sharifah Nurafizah Syed Annuar - Abd Malik, Akmal Nashren; Syed Annuar, Sharifah Nurafizah (UiTM Cawangan Johor, 2019)
In the era of technology revolution, e-wallet has become one of the top methods of payment used all over the world. However, its services are considered in the infancy stage and still relatively new to the Malaysian consumers. So far, limited studies can be found to measure the intention to use E-wallet in Malaysia. This paper seeks to examine the factors affecting consumers' intention towards the usage of e-wallet particularly among youth between 18-30 years old in Malaysia. In this study, perceived usefulness, perceived ease-of-use, perceived risk and trust will be examined to identify the relationships with consumers' intention to use an E-wallet in Malaysia. Technology Acceptance Model (TAM) will be used to construct the conceptual framework. This paper hopes to provide insights to the E-wallet literature by identifying factors influencing consumers' intention to use E-wallet